Mechanism and clinical application of thymosin in the treatment of lung cancer - Liu, Yafeng; Lu, Jibin (Frontiers in Immunology, 2023)
Cancer is one of the leading causes of death worldwide. The burden of cancer on public health is becoming more widely acknowledged. Lung cancer has one of the highest incidence and mortality rates of all cancers. The prevalence of early screening, the emergence of targeted therapy, and the development of immunotherapy have all significantly improved the overall prognosis of lung cancer patients. The current state of affairs, however, is not encouraging, and there are issues like poor treatment outcomes for some patients and extremely poor prognoses for those with advanced lung cancer. Because of their potent immunomodulatory capabilities, thymosin drugs are frequently used in the treatment of tumors. The effectiveness of thymosin drugs in the treatment of lung cancer has been demonstrated in numerous studies, which amply demonstrates the potential and future of thymosin drugs for the treatment of lung cancer. The clinical research on thymosin peptide drugs in lung cancer and the basic research on the mechanism of thymosin drugs in anti-lung cancer are both systematically summarized and analyzed in this paper, along with future research directions.